Strategi Perekayasaan Subak Sembung sebagai Daya Tarik Wisata di Perkotaan - NI LUH MADE AYU YULIANTARI PUTRI; I G.A. OKA SURYAWARDANI; I KETUT SURYA DIARTA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2020)
Subak Sembung Development Strategy As A Tourist Attraction In The Urban Area Tourism development in Bali is culture-based tourism. One of them is Subak SembungEcotourism which is located in Peguyangan Village, North Denpasar District, DenpasarMuniciplity. Its strategic location in the city center makes Subak Sembung facechallenges in land conversion. Development efforts needed to make Subak Sembung atourist attraction as well as a traditional organization in agriculture. The purpose of thisstudy was to identify the strengths, weaknesses, opportunities, and threats of SubakSembung, formulate alternative strategies, and determine priority strategies to developSubak Sembung as a tourist attraction in urban areas. The results of the SWOT matrixproduced several alternative strategies, namely market expansion, collaboration withgovernment and external entrepreneurs, developing agricultural-based touristattractions, holding promotions, arousing agricultural activities and religious rituals,development efforts that were in accordance with the awig-awig of subak, formingmanagement bodies of ecotourism, and selective in developing tourism facilities. Thepriority strategy based on QSPM analysis was to establish an ecotourism managementbody so that Subak Sembung could be developed with better facilities. Subak membertogether with the government and other stakeholders must take advantage of theopportunities and strengths they have in order to minimize the weaknesses and threatsfaced by Subak Sembung. Based on the results of the study, the suggestion that can bemade is to form a more creative ecotourism management body so that the appreciationand activities of the community can be developed for the sustainability of Ecotourism inSubak Sembung.